TALKING STICK : A LEARNING MODEL TO IMPROVE STUDENT'S MATHEMATICS LEARNING INTEREST AND ACHIEVEMENT IN ELEMENTARY SCHOOLS - Rika Wulandari (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to determine how the steps of the talking stick type of cooperative learning model assisted with question cards that can improve student learning outcomes and interest. The research was conducted using this type of classroom action research. The stages of classroom action research carried out include: plan, act, observe, reflect. The research was conducted at SDN Kara I, Sampang to 9 Grade III students. The results of the study indicate that the steps of the talking stick type of cooperative learning model assisted with question cards that can improve learning outcomes and student interest are: the teacher organizes students into several groups, each group consisting of four students heterogeneously. The teacher explains the rules of the game, namely the game is done by running a stick while singing, if the teacher says